CRIMINAL LIABILITY OF INVESTIGATORS IN CASES OF ERROR IN PERSONA ACCOMPANIED BY VIOLENCE: A CASE STUDY OF THE WRONGFUL ARREST OF A SNAIL COLLECTOR IN GROBOGAN - Ramadhani, Zaenu Agil; Sumardiana, Benny (Jurnal Meta-Yuridis, 2026)
Indonesia, as a state based on the rule of law (rechtsstaat), places the supremacy of law and the protection of human rights (HAM) as fundamental pillars in governance and law enforcement. However, in practice, serious violations that undermine these principles still frequently occur, including incidents of error in persona or wrongful arrest accompanied by acts of violence perpetrated by law enforcement officers. The wrongful arrest of a snail collector in Grobogan Regency serves as a concrete example of abuse of power by investigators, which contravenes the principles of due process of law and human rights.This study aims to analyze the criminal liability of investigators who commit wrongful arrest (error in persona) accompanied by violence and to elaborate on the legal remedies available for restoring the rights of victims, using the Wrongful Arrest of a Snail Collector in Grobogan as the case study. The research employs a normative legal method with a legal principles approach, examining statutory regulations (KUHAP, KUHP) and relevant doctrines concerning criminal liability, abuse of authority, and human rights protections.